Law enforcement against members of the National Police involved in narcotics is reviewed from the Regulation of the Chief of Police No. 14 of 2011 concerning the Code of Professional Ethics of the National Police and Government Regulation No. 1 of 2003 concerning the Dismissal of Police Members - Suharmoko, Tri; Pakpahan, Zainal; Siahaan, Nimrot (International Journal Labs, 2024)
This study discusses law enforcement against members of the National Police involved in drug abuse, with a review of the Chief of Police Regulation Number 14 of 2011 concerning the Code of Professional Ethics of the National Police and Government Regulation Number 1 of 2003 concerning the Dismissal of Police Members. The research method used is normative legal research. The results of the analysis show that law enforcement against members of the National Police who commit criminal acts of drug abuse refers to Law Number 35 of 2009 concerning Narcotics. In addition, violations of the National Police Professional Code of Ethics may result in ethical and administrative sanctions in accordance with the provisions stipulated in the regulation. Ethical sanctions are applied for minor violations, while administrative sanctions can include serious violations that can result in dishonorable dismissal of members of the National Police. The implication of this study is the importance of maintaining the integrity and professionalism of members of the National Police in carrying out their duties and complying with applicable legal rules in order to realize fair and effective law enforcement.